Damage and microstructure evolution of yttria particle reinforced tungsten plates under laser thermal shock - REN Daya; ZAN Xiang (Fenmo yejin jishu)
Yttria particle reinforced tungsten plates with different thickness reduction were prepared by powder metallurgy technology combined with rolling process. The prepared samples with different recrystallization volume fractions were subjected to transient laser thermal shock experiments to study the surface damage and microstructure evolution under the synergistic effect of recrystallization caused by long-term steady-state heat load and transient thermal shock. In the results, the cracks, melting, and other damages occur on the sample surface because of the thermal shock loading. Moreover, the recrystallization process would accelerate the widening of cracks and the enlargement of melting area, which greatly reduces the ability of the materials to resist transient heat loading. Under the same power density, the damage level of the samples with 67% thickness reduction is obviously lower than that with 50% thickness reduction, and the former has better thermal shock resistance; the molten zones of these two samples are composed by the columnar grains, which are associated with the grain size of the initial matrix below, and the columnar grains formed in rolled samples are finer and numerous, while those of the fully recrystallized samples are coarser.